Preparation of bread with the addition of edible flowers (@limentech, Ciencia y Tecnología Alimentaria, 2019)
In recent times, consumers have been looking for new food alternatives; these must be safe, nutritious and have sensory characteristics of quality.quality. For this reason, the consumption of flowers (florifagia) is gaining strength among the population. This is not a recent activity, since in many parts of the world the consumption of edible flowers continues as a tradition.edible flowers continues as a tradition (Caballero, 2009). This project has been developed by bakery apprentices from SENA, whose objective was to elaborate an innovative and healthy product, using products, textures, flavors and colors with possible functional properties that benefit the regular consumers of this product. Different techniques and procedures were used to standardize the formula and achieve the functional contribution.A product with good acceptance among the surveyed community was obtained, achieving the development of a product with pleasant innovative qualities as an alternative for those people who consume bread.
Keywords: Edible Flowers; Innovation; Bread; Baking